Assessment of malocclusion severity and orthodontic treatment needs in 12-15-year-old school children of Namakkal District, Tamil Nadu, using Dental Aesthetic Index - S Nagalakshmi; S James; C Rahila; K Balachandar; R Satish (Wolters Kluwer Medknow Publications, 2017)
Objectives: The present study was aimed to assess the severity of malocclusion and orthodontic treatment needs among 12-15-year-old schoolchildren in rural area of Namakkal district, Tamil Nadu, India, using the Dental Aesthetic Index (DAI). Materials and Methods: A cross-sectional study was conducted among a sample of 1078 schoolchildren (12-15 years of age) who were selected by two-stage cluster sampling technique. Severity of malocclusion and orthodontic treatment needs were assessed according to the DAI using a specially designed survey pro forma with the aid of the WHO's Oral Health Survey: Basic Methods. Based on the distribution of data, analysis of variance and unpaired student t-test were used. Results: Out of the total of 1078 children examined, 528 (49%) were males and 550 (57%) were females. The results indicate that 82.74% of the schoolchildren were found with little or no malocclusion requiring no orthodontic treatment. The gender-wise distribution of DAI score among children aged 12 years had significant difference between males (20.43 ± 3.67) and females (21.62 ± 4.335) (P = 0.015) and children aged 15 years also showed highly significant difference among gender (P = 0.000). Conclusion: Malocclusion not only impacts the appearance of the person but also affects the self-esteem and psychological well-being. This is the first step in understanding the treatment need so that further steps can be taken in preventive and interceptive care.